2011
DOI: 10.1002/j.0022-0337.2011.75.6.tb05107.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Development and Evaluation of Online Tobacco and Alcohol Modules for Dental Students

Abstract: Tobacco use and heavy alcohol consumption are major risk factors for the development of oral and pharyngeal cancer (OPC). Detection and modiication of these risks by dentists are keys in preventing OPC. While dentists are encouraged to screen patients for tobacco and alcohol use and educate them about the oral health risks they pose, dental students receive little formalized training in this area. This pilot project was designed to develop and evaluate two online training modules for dental students: one on to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Other studies have shown that dental students recognise they are role models in society, are conscious of their counselling role, and think they should receive tobacco control education and training in motivational counselling for tobacco cessation whilst in dental school (19–22). An online training module has been trialed recently and resulted in valuable improvement in dental students’ knowledge of tobacco but was unable to assess actual behavioural change (23). Increasingly, the important role of the dental practice team in tobacco use counselling is emphasised, with national and international associations taking leadership in promoting motivational cessation programs (24, 25).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that dental students recognise they are role models in society, are conscious of their counselling role, and think they should receive tobacco control education and training in motivational counselling for tobacco cessation whilst in dental school (19–22). An online training module has been trialed recently and resulted in valuable improvement in dental students’ knowledge of tobacco but was unable to assess actual behavioural change (23). Increasingly, the important role of the dental practice team in tobacco use counselling is emphasised, with national and international associations taking leadership in promoting motivational cessation programs (24, 25).…”
Section: Discussionmentioning
confidence: 99%
“…Gadbury‐Amyot and Brockman 52 reported a totally online pharmacology course that provided a positive learning experience with enhanced learning outcomes. Recently, Miller et al 59 found that two online training modules on tobacco and oral health risks and alcohol screening resulted in meaningful improvement in dental students’ knowledge of tobacco and alcohol use as well as alcohol screening methods. Additionally, it has been reported that online tests for self‐study purposes have been recommended and shown to improve students’ motivation 60 .…”
mentioning
confidence: 99%
“…Section IV combined two multiple choice questions and eight single-answer questions about alcohol knowledge as described by Miller et al . ( 13 ). The last section (VI) measured the stages of change.…”
Section: Methodsmentioning
confidence: 99%